P187 DRUCEBO EFFECT IN STATIN THERAPY: MORE ATTRIBUTABLE TO THE PATIENT, THE DOCTOR, OR THE MASS MEDIA?. (18th May 2022) - Cosmi, D; D'Orazio, S; Mariottoni, B; Tarquini, B; Cosmi, F
Abstract: In recent years, the term "drucebo effect" (drug + nocebo) has been coined to mean the nocebo effect attributable more to the patient's expectations, the doctor's preferences and the interference of the mass media rather than the actual pharmacological effect . We evaluated this effect in 9, 605 patients treated with statins, in primary (27%) and secondary (73%) prevention. Presumed statin intolerance was reported in 1, 729 patients (18%) with discontinuation of therapy for 5 days to 4 weeks. Table 1 shows the causes of the presumed intolerance and the related SMIS (Statin Myalgia Index Score). Patients with myalgia with or without CPK elevation and probable or possible SMIS were advised to halve the dose, with reassessment after 2–4 weeks. With persisting symptoms, the statin was changed. If symptoms were also present with the second statin, the patient was advised to take the drug every other day. In patients with unlikely SMIS, the decision to resume therapy was shared with the patient, informing him of the benefits of statins on mortality and morbidity. Probable true intolerance was found in 576 patients (6% of the overall population on statin therapy: 332 with myalgia with or without CPK elevation and SMIS probable, 152 with myalgia and CPK elevation with SMIS possible, 46 with asymptomatic CPK elevation, 15 transaminase increased, 21 with general malaise, 10 with severe depression). In 12% of patients, on the other hand, the interruption is attributable to a nocebo effect due to both the patient and the treating physician or other specialist, who are inclined to attribute the unwanted symptoms more to the drug than to other factors or to consider it non–modifiable by modifying the drug or the doses. Interference from the mass media is common, and it is difficult to distinguish a greater responsibility of one or the other.In patients treated with statins, a drucebo effect is frequently found, which is partly attributable to the patient, partly to the doctor and the mass media, who tend to attribute muscle symptoms to the treatment with statins and to interrupt therapy without taking into account the benefits regarding the reduction of mortality and morbidity found in numerous studies with indisputable evidence of efficacy and safety. In our study, a probable true intolerance to statins is found in about one third of patients who report symptoms.